Adverse Outcomes Associated With Nerve Stimulator–Guided and Ultrasound-Guided Peripheral Nerve Blocks by Supervised Trainees: Update of a Single-Site Database. Issue 6 (1st November 2012) - Orebaugh, Steven L.; Kentor, Michael L.; Williams, Brian A.
Abstract : Background: We previously published a retrospective review of complications related to peripheral nerve blocks performed by supervised trainees, from our quality assurance and billing data, guided by either ultrasound, with nerve stimulator confirmation, or landmark-based nerve stimulator techniques. This report updates our results, for the period from May 2008 through December 2011, representing ongoing transition to near-complete combined ultrasound/nerve stimulator guidance in a block-oriented, outpatient orthopedic anesthesia practice. Methods: We queried our deidentified departmental quality improvement electronic database for adverse outcomes associated with peripheral nerve blocks. Billing records were also deidentified and used to provide the denominator of total number of blocks using each technique of neurolocation. The types of blocks considered in this analysis were interscalene, axillary, femoral, sciatic, and popliteal-sciatic blocks. Nerve block complications based on each type of guidance were then compared for the entire recent 30-month time period, as well as for the 6-year period of this report. Results: There were 9062 blocks performed by ultrasound/nerve stimulator, and 5436 by nerve stimulator alone over the entire 72-month period. Nerve injuries lasting longer than 1 year were rare, but similar in frequency with both nerve guidance techniques. The incidence of local anesthetic systemic toxicity was found to be higher with landmark–nerve stimulator technique than with use of ultrasound-guided nerve blocks (6/5436 vs 0/9069, P = 0.0061). Conclusions: We report a large series of combined ultrasound/nerve stimulator nerve blocks by supervised trainees without major local anesthetic systemic toxicity. While lacking the compelling evidence of randomized controlled trials, this observational database nonetheless allows increased confidence in the safety of using combined ultrasound/nerve stimulator in the setting of anesthesiologists-in-training.